Lançamento tributário por arbitramento - Brito, Alysson Castro de (2019)
The present work aims to make an analysis of technique of the tax assessment with arbitration of the calculation base. This institute, expressly written Brazilian Internal Revenue Code, has not received much attention from national doctrine or jurisprudence, despite its great practical implications since it is a form of tax credit formalization widely applied by all public tax Treasury departments entities, although it does not have extensive regulation on the legislation, apart from its simple authorization. This work assumes the premise that law is a language phenomenon and, therefore, can be analyzed by semiotics, a tool that helps to better analyze this type of tax assessment. The arbitration of the basis of calculation is an example, as defended here, of the use of the principle of practicability in tax law, allowing the law to be practicable in the pursuit of general taxation and equality, at times when its regular incidence would not be possible due to the absence of a method to correctly measure the basis for the taxation or when it is suspected that the taxpayer may be providing untrue information. It relates also to various other principles such as legality, legal certainty, ability to pay, reasonableness and morality. Arbitration of the basis of calculation is understood here not as a mode to formalize the tax debt, but rather as an indirect method of gauging this portion of the quantitative criterion, which requires the use of practicability instruments such as presumptions, fictions, indeterminate legal concepts. For the study of this institute, an analysis of both national and alien doctrine is paramount. Comparative law is also a rich source, being used to make parallels whenever possible. Aspects of administrative binding and discretionary behavior as well as their boundaries are also debated. Justifications for its existence are presented, hypotheses of appropriateness are addressed, defenses of the taxpayer are examined and concrete examples of their application, both adequate and inadequate, are criticized. A brief analysis of the case law of the higher courts on the subject is also discussed at the end, followed by the conclusions reached